In vitro and In vivo biological activities and phenolic characterization of Thymus praecox subsp. skorpilii var. skorpilii - RAYAMAN, ERKAN; ÇAM, MUHAMMET EMİN; TAŞKIN, TURGUT (SPRINGER, 2019)
Thymus species are used as food and spices in several Mediterranean and other countries as well as for medical purposes on account of their biological properties. The extraction procedures and solvents are an important step in processing bioactive constituents from the plant materials. Therefore, the aim of this study was to evaluate in vitro antioxidant, anticholinesterase, antimicrobial, anti-urease and in vivo anti-inflammatory activities of Thymus praecox subsp. skorpilii var. skorpilii using a variety of extracts. In addition, the phenolic characterization of the fraction methanol extract, which showed the highest phenolic contents and the strongest antioxidant and anticholinesterase activity were performed by HPLC-DAD and LC-MS/MS techniques. In the present study, the fraction methanol and direct methanol extracts exhibited strong DPPH, ABTS, and ferric reducing activity and strong antibacterial activity against Staphylococcus epidermidis strains. The fraction chloroform and fraction petroleum ether extracts showed the strongest anti-urease activity and also, the petroleum ether extract exhibited strong antibacterial activity against the Staphylococcus aureus strain. The fraction methanol and direct methanol extracts showed in vivo anti-inflammatory activity very similar to each other. As a result of this study, chlorogenic acid, luteolin-7-O-glucoside, 3-O-feruloylquinic acid, quercetin-3-O-hexoside, and apigenin-7-O-glucuronide compounds were analyzed for the first time in the methanol extract of the plant. This latter study revealed the effects of the extraction methods and phenolic compounds on its biological properties.
Keywords: Biological activity; HPLC-DAD-MS; Thymus praecox subsp; skorpilii var; skorpilii; ANTIOXIDANT ACTIVITY